2 - Marginal Youths or Outlaws? Youth Street Gangs, Globalisation, and Violence in Contemporary Sierra Leone - Abdullah, Ibrahim (Africa Development, 2020)
Sierra Leoneans were shocked when video clips of the Central Correctional Centre gallows began circulating on social media after the Minister of Internal Affairs instructed the prison authorities to get ready to take life. The Minister’s pronouncement came hot on the heels of a series of alleged gang-related murders that rocked Freetown in 2016. What are the complex linkages between street violence and youth marginalisation? How might violence among marginal youth relate to unplanned urbanisation, the retreat of the state, the neoliberal paradigm, and the wider political economy – all trappings of an exclusionary globalisation process that continues to exclude those at the periphery? This article describes the appropriation by marginal actors of global cultural influences and their transcription into deadly weapons of the weak in furtherance of a survivalist objective anchored in citizenship. The research is based on fieldwork conducted in five cities in Sierra Leone – group discussions and in-depth interviews with over 300 participants, all identifying themselves as gangsters belonging to one of the three dominant team/ set federations: Crip, Blood, and Black (Black Hood or Black Game). Problematising their quotidian existence in contemporary Africa raises fundamental questions about globalisation and citizenship in the making of subaltern subjectivities.